Data Mining Menggunakan Algoritma K-Means Clustering dalam Analisis Tingkat Potongan Harga Terhadap Harga Jual Sepeda Motor Honda - Rafki Mauliadi (Jurnal Informatika Ekonomi Bisnis, 2022)
Knowledge Discovery in Database (KDD) has a structured analysis process to obtain the latest information. Data mining plays a role in extracting hidden information with one method, namely clustering. The purpose of this study was to determine the appropriate level of discount for each type of Honda motorcycle. The data processed in this study were sourced from the Marketing Main Dealer for Honda Motorcycles, West Sumatra. Furthermore, this data is processed by the Data Mining technique using the K-Means Clustering Algorithm. The processing stage is to determine the number of clusters and centroids, then calculate the distance between the centroid point and each object in the data. Predefined objects are grouped to determine cluster members based on distance. The calculation is continued until the resulting centroid value remains and the cluster members do not move to another cluster. The results of testing this algorithm are 3 clusters with 42 test data, in cluster 1 there are 34 types of vehicles that get discounted prices, then cluster 2 of 7 types of vehicles can get discounts and cluster 3 of 1 type of vehicles can not get discounts. The analysis of the test results has been able to determine the level of discount on the selling price of Honda motorcycles. By grouping customer interest data, it can be recommended to provide discounted sales prices in order to help marketing management increase sales of Honda motorcycles.